Self-Control: The Linking of Self, Motivation, and Virtue - Cole Wright, Jennifer; Nadelhoffer, Thomas; Goya-Tocchetto, Daniela; Langville, Amy; Struchiner, Noel (My University, 2015)
The key issue our team will be exploring is the role played by self-control in the development and expression of virtue. In particular, we are interested in the self-regulating function of people’s self-narratives (specifically, the degree to which these narratives weave together virtue-oriented goals and identity attributes). We expect to find that highly virtue-oriented self-narratives help to generate and maintain the motivational structure necessary for virtuous character. In order to test this hypothesis, we will refine and develop measures to investigate the relationship between virtue-relevant mental states/behaviors, general capacities for self-control, and self-narratives. Having developed the requisite psychometric tools, we will then extend our research by exploring the relationship between self-control, self-narrative, and virtue cross-culturally. By comparing Americans and Brazilians, we hope to determine whether general self-control and self-narratives play a consistent and stable role in the development of virtue (or whether there are instead important cultural differences). Finally, we will rely upon recent advances made in computational linguistics to explore how people think and talk about virtue. Our goal at this final stage is two-fold: First, we want to explore the underlying semantic and syntactical structure of people’s self-narratives and the relationship between how people think and talk about self-control and how they behave. Second, we want to develop therapeutic writing tools for shaping and changing people’s self-narratives in the hopes that these changes will in turn improve self-control and facilitate virtuous behavior (in children, adolescents, and adults). In this respect, our project has a descriptive element as well as a prescriptive element.
This presentation was delivered at the Self, Motivation & Virtue Project's 2015 Interdisciplinary Moral Forum, held at Marquette University in Milwaukee, Wisconsin.
Keywords: Philosophy; Psychology, Cognitive.